Theatre & sexuality - Dolan, Jill 1957- (Houndmills, Basingstoke, Hampshire, United Kingdom Palgrave Macmillan, 2010)
"This book explains the critical validity of using sexuality as a lens for examining theatres creation and reception. The book offers clear introductions to sexual identity politics, ways of reading sexuality on stage and a select history of LGBTQ theatre, including a reading of Split Britches/Bloolips production Belle Reprieve"--Provided by publisher.
Gay and lesbian lives and ideas in the twentieth century -- Plays and productions : on and off Broadway -- From the avant-garde to commercial theatre -- Belle reprieve : LGBTQ theory into practice -- New audiences : no longer preaching to the choir.
Includes bibliographical references and index.
Keywords: Gays and the performing arts; Gay theater -- United States; Gay theater -- Great Britain; Homosexuality and theater; Sex role in the theater; Sex in the theater